Regulation of FN1 degradation by the p62/SQSTM1-dependent autophagy-lysosome pathway in HNSCC - Xinchen Liu; Lin Meng; Xing Li; Daowei Li; Qilin Liu; Yumeng Chen; Xiangwei Li; Wenhuan Bu; Hongchen Sun (Nature Publishing Group, 2020)
Abstract Epithelial-mesenchymal transition (EMT) is involved in both physiological and pathological processes. EMT plays an essential role in the invasion, migration and metastasis of tumours. Autophagy has been shown to regulate EMT in a variety of cancers but not in head and neck squamous cell carcinoma (HNSCC). Herein, we investigated whether autophagy also regulates EMT in HNSCC. Analyses of clinical data from three public databases revealed that higher expression of fibronectin-1 (FN1) correlated with poorer prognosis and higher tumour pathological grade in HNSCC. Data from SCC-25 cells demonstrated that rapamycin and Earle's balanced salt solution (EBSS) promoted autophagy, leading to increased FN1 degradation, while 3-methyladenine (3-MA), bafilomycin A1 (Baf A1) and chloroquine (CQ) inhibited autophagy, leading to decreased FN1 degradation. On the other hand, autophagic flux was blocked in BECN1 mutant HNSCC Cal-27 cells, and rapamycin did not promote autophagy in Cal-27 cells; also in addition, FN1 degradation was inhibited. Further, we identified FN1 degradation through the lysosome-dependent degradation pathway using the proteasome inhibitor MG132. Data from immunoprecipitation assays also showed that p62/SQSTM1 participated as an autophagy adapter in the autophagy-lysosome pathway of FN1 degradation. Finally, data from immunoprecipitation assays demonstrated that the interaction between p62 and FN1 was abolished in p62 mutant MCF-7 and A2780 cell lines. These results indicate that autophagy significantly promotes the degradation of FN1. Collectively, our findings clearly suggest that FN1, as a marker of EMT, has adverse effects on HNSCC and elucidate the autophagy-lysosome degradation mechanism of FN1.